Odious Loans between Legal Legitimacy and Financial Sustainability - Idelbi, Mona (Journal of Legal Sciences, 2025)
The phenomenon of odious debt has long posed a dilemma for international law and global financial governance. Although many developing and post-conflict countries have endured the burden of illegitimate loans contracted by authoritarian regimes, the concept of “odious debt” has not been formally recognized under international law. This raises a fundamental legal and ethical question: should successor governments and their citizens be bound by debts incurred without popular consent, often used to finance repression, corruption, or wars against their own populations? Against this background, the present study explores the legitimacy of odious loans and their broader implications for financial sovereignty, human rights, and sustainable development. The study concludes that odious debt remains primarily a moral and political principle rather than a binding legal rule. Nevertheless, its recognition could serve as a foundation for greater financial justice and international accountability. The findings underscore that such debts undermine development, violate human rights, and perpetuate inequality, while creditor states often evade responsibility. The research recommends advancing toward codification of the doctrine within international agreements, clarifying its legal bases through principles such as unjust enrichment and abuse of rights, and creating mechanisms for debt repudiation or cancellation. Ultimately, embedding the principle of odious debt into international financial governance could not only relieve debtor states of unjust obligations but also promote sustainable development and protect future generations from the consequences of illegitimate borrowing.